Basketball - Gifford, Clive (New York PowerKids Press, 2009)
Basketball is an all action team sport. Five players on each team dribble and pass a basketball around a court, trying to get into a position to shoot at the basket and score points. The team with the most points at the end of the game wins. If the scores are level at the end, one or more periods of overtime are played until one team wins.
5 - 9
Keywords: Basketball